Infectious pathogen detection arrays: viral detection in cell lines and postmortem brain tissue. (November 2005) - Conejero-Goldberg, Concepcion; Wang, Ena; Yi, Chuli; Goldberg, Terry E.; Jones-Brando, Lorraine; Marincola, Francesco M.; Webster, Maree J.; Fuller Torrey, E.
A unique array-based pathogen chip has been developed for the detection of viral RNA or DNA relevant to pathologies of the central nervous system. A total of 715 unique oligonucleotides (60-mer) representing approximately 100pathogens were designed based on open reading frames (ORFs)from highly conserved and heterogenic regions within viral families. In addition, viral genes reflecting different stages of pathogen infection were also included to potentially define the stage of the viral infection. Viruses (double-stranded DNA, double- or single-stranded RNA, delta, retroid), parasites, and bacteria were included. Test samples labeled with Cy™5 were examined by cohybridization with a reference RNA, labeled with Cy3, to the pathogen microarray chip. Good reproduc-ibility of experiments was observed, based on data generated from duplicate hybridizations and duplicate spots on the microarray platform. A viral transcript detection sensitivity of 1 ×10 3 plaque-forming units (pfus) was achieved using selected cell lines and viruses. These findings suggest that the array-based platform described here is capable of detecting a broad spectrum of viruses in a single assay with relatively high sensitivity, specificity, and reproducibility. This method may be used to provide evidence of viral infection in postmortem tissue from psychiatric patients as well as a wide range of other diagnostic categories.